Causes of misdiagnosis in assessing tubal patency by transvaginal real-time three-dimensional hysterosalpingo-contrast sonography - Liang,Na (2019)
SUMMARY OBJECTIVE This study aims to investigate the causes of misdiagnosis in assessing tubal patency by transvaginal real-time three-dimensional hysterosalpingo-contrast sonography (TVS RT-3D-HyCoSy), in order to improve the diagnostic efficiency of TVS RT-3D-HyCoSy. METHODS A total of 162 oviducts of 83 infertility patients were examined by TVS RT-3D-HyCoSy. These results were compared with the gold standard for laparoscopic dye studies, and the misdiagnosed cases were analyzed. RESULTS TVS RT-3D-HyCoSy revealed that 68 oviducts were unobstructed and 94 obstructed. The results for the 144 oviducts were in line with the gold standard, while those for 18 oviducts were not. The accuracy rate of the TVS RT-3D-HyCoSy was 88.9%, and the misdiagnosis rate was 11.1%. The main causes of misdiagnosis included contrast medium countercurrent and diffusion, oviduct spasm, abnormal shape or position of the oviduct, pelvic adhesion, and poor imaging operation. CONCLUSION TVS RT-3D-HyCoSy can well-evaluate tubal patency, and understand and improve the cause of misdiagnosis. Furthermore, the diagnostic efficiency of TVS RT-3D-HyCoSy can still be further improved.